Influence of Partner Characteristics and Relational Capital on the Success of Business/Nonprofit Organization Partnerships - María Jesús Barroso-Méndez; Clementina Galera-Casquet; Víctor Valero-Amaro; María Teresa Nevado-Gil (Complexity)
The 2030 Agenda for Sustainable Development is the largest framework of global cooperation for human and environmental development on a global scale. This framework requires new responses in the social and political spheres. To a large extent, these can come from different economic and social sectors working together to create synergies that will allow quantitatively significant progress to be made towards the United Nations’ Sustainable Development Goals (SDGs). Because of that, in the last few decades, the number of cross-sector social partnerships, and, in particular, partnerships between businesses and nonprofit organizations (NPOs), has increased enormously. However, despite their importance, a large proportion of these partnership processes have been unsuccessful due to the different characteristics of the partners and the relational complexity involved in the multiple factors that affect the collaboration over time. In this regard, the business-NPO literature has stressed the importance of improving the existing understanding of the main factors which favour a partnership’s success as well as the interrelationships among those factors. Following different theoretical perspectives used mainly in the context of business-to-business collaborative relationships, the authors test how partner characteristics indirectly influence the success of the partnerships through relational capital. The results, based on a sample (n = 102) of Spanish businesses in collaboration relationships with NPOs, show that partner characteristics (shared values and resource complementarity) help in the formation of relational capital (trust, information sharing, and commitment), and that this positively influences the success of such partnership processes (achievement of objectives and satisfaction of the partners).